The pirate jamboree - Teague, Mark (New York : Orchard Books, 2016)
Pirates Blackbeard Johnson and his brothers, Eyepatch Sue, and others sail over to Peg Leg Jones' for a happily chaotic pirate jamboree--until the S.S. Clean Your Room (otherwise known as Mrs. Jones) arrives and playtime is definitely over.
School Library Journal, April 2016
Booklist, March 2016
New York Times, September 2016
Publishers Weekly Annex, March 2016
3.0
K-3
Keywords: Pirates -- Fiction; Play -- Fiction; Imagination -- Fiction; Pirates -- Fiction; Play -- Fiction; Imagination -- Fiction; Stories in rhyme; Picture books